A preliminary investigation of the effects of different type of training in Auditory Brainstem Response (ABR) waveform analysis among audiology students - Dzulkarnain, Ahmad Aidil Arafat; Wan Mohd Pandi, Wan Mahirah; Wilson, Wayne J.; Bradley, Andrew P.; Sapian, Faizah (2014)
Training for audiology students in ABR waveform analysis is a challenging task. Traditionally, an instructor will spend few hours with students in tutorial and practical sessions to teach techniques for ABR waveform analysis. These include technique to determine the absence or presence of ABR and later technique to select the respective ABR peaks. One of the alternative methods to assist student to acquire the above skills is by using simulator training. This study is aimed to investigate the effects of different types of training (manual, ABR simulator training and combination of manual and simulator training) on Audiology student performance in ABR waveform analysis. Fourteen third-year audiology students were recruited in this study. The participants were divided into three different training groups based on their performance in the pre-training examination before underwent an eight hours of training sessions. All subjects were tested again to obtain their post-training examination score. The results showed that the post-training examination score was significantly higher than the pre-training examination score in the manual and combination of manual and ABR simulator training group (p < 0.05) but not in the simulator training group. This study’s concluded that a live instructor could still be required in the simulated training if this type of training to be successful.